COVID-19 impact on labour relations in Palestine, the need for legal reform - Mahmoud Fayyad; Abdel Raouf Al-Sinnawi (Heliyon, 2021)
Objective: This research aims to examine how lawful the measures taken by employers against workers are in the context of the COVID-19 pandemic, and to assess performance of the Ministry of Labour (MoL) and various trade unions in representing workers’ interests. Methodology: After an intensive literature review on the subject, 12 cases – representing different areas and economic sectors in the West Bank – were investigated. Then, free discussions were conducted with a focus group of 24 stakeholders (employers, employees, MoL representatives, trade union representatives, businessmen association representatives, lawyers, judges, and academics) to explore decisions made against employees, examine how lawful these decisions are, and present the evaluation of these groups to the MoL and trade unions. The discussions were followed by a quantitative questionnaire for 297 employees who were affected by unfair decisions and 87 employers representing different areas and sectors in the West Bank. A brainstorming session, involving two judges, two lawyers and four legal academics, was held to discuss research outcomes and benefit from their feedback and recommendations. Research problem: To demonstrate how lawful the measures taken by employers against workers are in the context of the COVID-19 pandemic, and to assess performance of the MoL and various trade unions in representing workers’ interests. Findings: The research paper reveals the illegality of the measures taken against employees in the context of responding to the economic effects of the pandemic. It reflects clear and significant dissatisfaction with the decisions made by trade unions and the MoL. The paper also recommends that some amendments need to be introduced to the Palestinian Labour Law. Originality/value: This research paper pursues the illegality of decisions made by employers against workers in the context of addressing the economic losses caused by the pandemic. It concludes that ambiguous provisions of the Palestinian Labour Law were a main factor that allowed employers to abuse these decisions. The tripartite agreement organised by the MoL was against workers interest and gave rise to many legal and economic challenges. The need to review the structure and functioning of trade unions in the West Bank is highlighted in this research paper.